A Decision Making System For Selecting Computer Components Combination To Obtain Benchmark Score Suitable For Requirements Using SAW Method Based On Web Data: Sistem Penentuan Keputusan Dalam Pemilihan Kombinasi Komponen Komputer Untuk Mendapatkan Skor Benchmark Sesuai Kebutuhan Dengan Metode SAW Berbasis Web - Dicky Mardianto, Sigit; Untari N , Dewi Handayani (Universitas Muhammadiyah Sidoarjo, 2024)
ABSTRACT Computer components are devices that are currently indispensable for almost all human needs. In its development, computer components have had a significant increase in data processing capabilities, which sometimes makes the period of use of computer components that comply with minimum specifications shorter. How could it not be, when a new computer component is launched by the company that makes it, then within one to two years the company that makes it has launched a new computer component product with higher specifications and higher efficiency. This can also cause an increase in electronic waste due to computer components that can no longer meet needs. Then, in terms of the software used, there was also a significant increase, forcing component users to replace the computer components used with computer components that have specifications that match the needs of the software used. Thus, I feel the need to help computer component users so that they can determine a good combination of computer components, so that they can achieve the computer component requirements required by the software used. Keywords: Computer Components, Software, Electronic Waste.